Siderite precipitation using by-product red gypsum for CO2 sequestration. (March 2018) - Rahmani, Omeid
Highlights: Increasing the reaction temperature caused to increase the purity of FeCO3 . The results revealed that the RG is feasible to produce FeCO3 . The maximum product purity is achieved at optimum reaction time of 150 min. Abstract: In this research, the feasibility of CO2 mineral carbonation by the use of by-product red gypsum (RG obtained from Huntsman Tioxide, Terengganu, Malaysia) to form iron carbonate (FeCO3 ) was evaluated. Toward this aim, the wide-range conditions of key procedure variables such as reaction temperature, reaction time, and CO2 pressure on the rate of mineral carbonation were studied. In addition, preliminary analyses on red gypsum were carried out to determine its physical and chemical characteristics. The feasibility of direct carbonation of RG to form FeCO3 was assessed at different CO2 pressures of 1 to 70 bar and different reaction temperatures of 25 to 200 °C to discover the effects of the key functions on overall direct carbonation. In general, increasing CO2 pressure to 10 bar was found to increase the overall FeCO3 purity and carbonation efficiency to 97% and 98%, respectively. Moreover, the reaction temperature affected the conversion rate at two different functions. First, FeCO3 purity and its carbonation efficiency increased to the maximum values when the reaction temperature increased to 150 °C, and then they were slightly decreased to 91% and 92%, respectively, with increase of temperature to 200 °C. The results also showed that the maximum product purity is achieved at optimum reaction time of 150 min.